Thermal performance analysis of heat pipe heat exchanger for effective waste heat recovery - Geum, Gyohoon; Kang, Sukkyung; Cho, Sehyeon; Kong, Daeyoung; Lee, Seungjae; Seo, Jin Hyeuk; Shin, Dong Hwan; Lee, Seong Hyuk; Lee, Jungho; Lee, Hyoungsoon (International Communications in Heat and Mass Transfer, 2024)
The importance of waste heat recovery systems for various industrial processes has been growing steadily, driven by their potential to improve energy efficiency, reduce fuel consumption, and minimize environmental impacts. Heat exchangers are key components in these systems, facilitating the transfer of heat from waste sources to useful media. Among them, heat pipe heat exchangers (HPHX) have been widely employed in industries such as steel and ceramic as an energy-saving measure to cut carbon emissions. Previous studies have mainly focused on experimental analyses of HPHX thermal performance. However, due to the high cost of full-scale thermal tests, there is a lack of research investigating the effect of detailed geometrical and operational variations on HPHX thermal performance. This study addresses the existing gap by conducting a comprehensive conjugate numerical investigation to explore the influence of flow path structure and condenser area on the performance of an air-to-liquid HPHX. We first utilize a full-scale conjugate simulation to propose an optimized HPHX design that enhances both heat transfer rate and effectiveness through the variation of baffle configurations and condenser height. Subsequently, we experimentally validate the proposed design through a full-scale HPHX thermal test. Results revealed that the baffle design significantly improved the heat transfer rate and effectiveness by up to 36.3% and 36.0%, respectively. Conversely, increasing the condenser height by five times enhanced the heat transfer rate by only 3.5%, with the condenser area showing a minor impact owing to the higher heat capacity rate of water compared to air. The outcomes revealed remarkable energy-recovery capabilities, revealing a total thermal energy wastage recovery rate up to 19.7 kW. These findings demonstrate the potential and effectiveness of the proposed HPHX in waste heat recovery applications.
Keywords: Boiling heat pipe; Effectiveness; Heat pipe heat exchangers; Heat transfer rate; Industrial processs; Thermal Performance; Thermal performance analysis; Thermal tests; Waste heat recovery systems; Waste-heat recovery; Boiling heat pipe; Effectiveness; Heat pipe heat exchanger; Thermal performance; Thermosyphon; Waste heat recovery